Child Care Subsidies, Wages, and Employment of Single Mothers - Erdal Tekin (Institute for the Study of Labor (IZA), 2002)
This paper provides a comprehensive analysis of employment and child care payment decisions of single mothers in the early post-welfare reform environment, using data from the National Survey of America?s Families (NSAF). I develop and estimate a model that examines the effects of the price of child care and the wage rate on employment decision as well as the decision to use paid child care among single mothers. The model distinguishes between the full-time and part-time employment decisions as well as the prevailing wages in these two employment markets. A semi-parametric random effects estimator and the Gaussian Quadrature are used together to estimate the system of equations for the discrete outcomes of full-time and part-time employment, and child care payment, and the linear equations of the price of child care, and part-time and full-time wages in a unified framework. The econometric model also controls for the endogeneity of child care subsidy receipt and adjusts the hourly price of child care for the amount of subsidy for mothers who receive one. The results show that full-time working mothers are more sensitive to the price of child care than part-time working mothers. A lower price of child care leads to increases in overall employment and the use of paid child care. However, much of the increase in employment is in the form of full-time employment. An increase in the full-time wage rate leads to increases in overall employment and the use of paid child care. The effects of full-time wage rate are estimated to be much larger than those of the price of child care. Part-time wage effects are found to be so small to have significant implications.
Keywords: C14; J23; J13; 330; child care; employment; wages; child care subsidies; Frauenerwerbstätigkeit; Alleinerziehende; Arbeitszeit; Kinderbetreuung; Arbeitsangebot; Familienleistungsausgleich; Schätzung; Vereinigte Staaten